A Flexible Strategic Framework for Urban Heritage Management in Karbala Post-Pandemic: A Participatory Digital Approach to Achieving Urban Sustainability (Architecture Image Studies, 2025)
This study examines the reality of urban heritage management in Karbala, a city steeped in religious and historical significance. Karbala faces complex challenges, including rapid urban expansion, heavy seasonal visitor traffic, and the deterioration of infrastructure and historical fabric, all within a fragile institutional and economic context exacerbated by the COVID-19 pandemic, threatening the sustainability of its urban identity. The study aims to build a flexible and sustainable strategic framework for revitalizing urban heritage by integrating participatory governance, digital technologies, and environmental and economic dimensions into city management. It adopted a mixed methodology (quantitative and qualitative) that included questionnaires, interviews, geographic information systems analysis, and an assessment of urban sustainability indicators. The results revealed weak institutional integration, low community trust, limited use of digital tools in planning and management, and a near-total reliance on religious tourism. The study recommended establishing a participatory coordination framework, developing digital platforms, leveraging augmented reality technologies, diversifying the local economy through cultural industries, and reviewing urban legislation. The study contributes to aligning Karbala's uniqueness with global trends to achieve Sustainable Development Goal 11.4, and strengthening alliances between academics, authorities, and society towards a more resilient and just urban future.